Hemispheric lateralization of spatial attention in right- and left-hemispheric language dominance - Flöel, A.; Buyx, A.; Breitenstein, C.; Lohmann, H.; Knecht, S. (Behavioural brain research, 2005)
Hemispheric lateralization of the neural systems supporting language and spatial attention most commonly dissociate in healthy individuals. However, the reverse pattern with association of language and attention within the right hemispheres has also been observed. We investigated in 75 healthy volunteers (37 right-handed, 38 left-handed) if language and spatial attention may associate not only in individuals with an atypical pattern of language lateralization, but also in subjects showing the standard, i.e. left-hemispheric dominance for language. Hemispheric lateralization of cerebral perfusion was determined with functional transcranial Doppler ultrasonography during a visuospatial attention, and a word generation task. We found that language and visuospatial attention associated within the left hemisphere in five subjects and within the right hemisphere in eight subjects. We conclude that all combinations of cerebral lateralization for language and attention may exist in the healthy brain.